APPLICATION OF LAKES SYSTEM IN PREPARATION OF HAIR DYES POMADE CREAM OF FREEZE-DRIED RED DRAGON (Hylocereus polyrhizus) FRUIT PEEL JUICE AND ACUTE DERMAL IRRITATION - Malinda Prihantini; Muhammad Ikhsan; Hasan Abdul Karim; Sindi Fadillah Rianis; Sobari Sobari; Faykar Rheza (Universitas Muhammadiyah Magelang, 2024)
Dyes used in market products are mostly synthetic, which can irritate the skin and in the long term increase the risk of skin cancer. The peel of dragon fruit contains the red-violet pigment Betacyanin, which is potential as hair dyes but extremely sensitive to light and oxygen. The lakes system is the option to overcome the problem and increase the stability of pigments. The objective of this study was to learn about the use of the lakes system in the preparation of hair dyes pomade cream of freeze-dried red dragon fruit peel juice and its irritation aspect on skin. The lakes system was made with a 50% red dragon fruit peel juice, mixed with 5% alucol, then dried with 45% aerosil. Pomade cream was prepared by mixing oil phase and water phase at a temperature of ±60 °C with continuous mixing in 600 rpm for 10 minutes. Formula III is the bases without freeze-dried red dragon fruit peel juice. The non-lakes system of freeze-dried red dragon fruit peel juice was added to the bases for the FII, while the lakes system was added for the FI. Hair dyes pomade cream of red dragon fruit peel juice prepared in the lakes system has superior properties to the formula prepared without the lakes system. It demonstrated better homogeneity and softer texture, in addition acceptable skin pH range. The lakes system is suitable for the preparation of natural hair dye cream and does not irritate the skin.